2020
DOI: 10.3390/ijms21165662
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP2 Polymorphisms Are Associated with Clinical Characteristics and Development of Oral Cancer

Abstract: Insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2) is associated with insulin resistance, lipid metabolism, and tumorigenesis. However, the association between the IGF2BP2 polymorphism and oral cancer risk remains unclear. We recruited 1349 male patients with oral cancer and 1198 cancer-free controls. Three single nucleotide polymorphisms IGF2BP2 rs11705701, rs4402960, and rs1470579 were assessed using real-time polymerase chain reaction. The results indicate that the male patients with oral cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Studies have shown that IGF2BP2 is associated with immune cell infiltration in esophageal cancer [ 18 ]. In addition, a recent study conducted in Taiwan reported that the genetic polymorphism of IGF2BP2 is associated with less favorable clinical features and prognosis of patients with OSCC [ 19 ]. However, there is limited evidence regarding the association between IGF2BP2 and OSCC, and the role of IGF2BP2 in OSCC tumorigenesis has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that IGF2BP2 is associated with immune cell infiltration in esophageal cancer [ 18 ]. In addition, a recent study conducted in Taiwan reported that the genetic polymorphism of IGF2BP2 is associated with less favorable clinical features and prognosis of patients with OSCC [ 19 ]. However, there is limited evidence regarding the association between IGF2BP2 and OSCC, and the role of IGF2BP2 in OSCC tumorigenesis has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of IGF2BP2 is significantly upregulated in head and neck squamous cell carcinoma (HNSC) tissue and predicts a poor prognosis ( 12 ). In addition, IGF2BP2 polymorphisms are associated with adverse clinical features and the development of oral cancers ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pro-inflammatory cytokine interleukin 8 and related SNP is associated with the susceptibility of oral squamous cell carcinoma [ 36 ]. In addition, the higher Insulin-like growth factor 2 mRNA-binding protein 2 was found in head and neck squamous cell carcinoma and correlated with higher cancer stage and larger tumor size [ 17 ], while the presence of ADAMTS14 SNP rs12774070 was significantly associated with the degree of oral tumor cell differentiation [ 37 ]. In addition, gene-environment interactions exist in oral cancer; CD44 polymorphisms and betel quid chewing or tobacco smoking enhance the susceptibility to oral cancer occurrence [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other types of cancers, the environment as well as genetic factors will influence the clinical presentation and disease severity of oral cancer [ 12 , 13 , 14 , 15 , 16 ]. For instance, the insulin-like growth factor 2 mRNA-binding protein 2, a protein that contributes to insulin resistance and lipid metabolism, was related to less favorable clinical characters for oral cancer [ 17 ]. Additionally, the genetic polymorphism of chemokine receptor-2 gene enhances the susceptibility of oral cancer development [ 18 ].…”
Section: Introductionmentioning
confidence: 99%